Mu’jizatu Yasû’ ‘n al-‘Ilâj al-Jismâniy fî al-Kâtûlîkiyyah - Jarman Arroisi; Dea Felaputri (Journal of Comparative Study of Religions, 2020)
This article aims to examine non-medical healing as a miracle of Jesus. According to Christianity, non-medical healing is always being associate with miracles, also called divine healing which consists of healing physical and spiritual illness. Both are important parts of Christ's ministry. Jesus' ministry on earth, marked by healing, miracles, and miraculous signs. With descriptive and analysis methods, this study concludes that healing is a renewal of the body's condition to restore the strength of disease, and miracles are events that are difficult to reach by human reason. The relationship between Jesus' miracles and healing services in the Church is that there are several miracles of Jesus that have shown that faith and physical healing are interrelated. Healing from Jesus is not always instant because faith is a significant factor in getting healthy. One form of Jesus' healing is the law of touch and transmission, which is the means to make miracles. Not only that, but prayer is also a way to get healing from a distance. God wants the Church to fully operate on this earth as the empowered body of Jesus. For this to achieve, the gift and anointing of the Holy Spirit in believers must be activated. So that divine healing services can work in the Church along with traditional medicine while still being inseparable from the Christian faith.